Radiotherapy and immunotherapy: a synergistic effect in cancer care. Issue 1 (12th December 2018) - Turgeon, Guy‐Anne; Weickhardt, Andrew; Azad, Arun A; Solomon, Benjamin; Siva, Shankar
Summary: Radiotherapy is an effective treatment modality commonly used in efforts to cure many localised cancers and in the palliation of symptoms in metastatic cancers. Immunotherapy has revolutionised cancer care by increasing the disease control and overall survival of patients in several cancer types; however, the majority of patients do not respond to currently available therapies based on immune checkpoint inhibitors (ICIs). The benefit of those agents is limited to patients who have a pre‐existing active immune microenvironment that can be reactivated by ICIs. It is now recognised that radiotherapy does not only directly kill tumour cells but it also changes the tumour microenvironment, enhancing tumour cell recognition by the immune system and, therefore, acting as an in situ vaccine. Radiotherapy increases expression of tumour‐associated antigens, causes the release of cytokines, stimulates recruitment of dendritic cells and, most importantly, stimulates the proliferation and priming of cytotoxic CD8+ T cells in the tumour microenvironment. This immunological cascade specifically generates activated T cells able to induce immunogenic cell death directed against cancer cells bearing those antigens. By its ability to overcome some tumour immune escape mechanisms, radiation provides a non‐pharmacological and cost‐effective approach to potentially improve the systemic response to immune checkpoints inhibitors.